Chest Exercises: Movement and Loading of Shoulder, Elbow and Wrist Joints - Pascal Schütz; Pia Zimmer; Fabian Zeidler; Michael Plüss; Katja Oberhofer; Renate List; Silvio Rene Lorenzetti (MDPI AG, 2022)
Injuries to the shoulder are very common in sports that involve overhead arm or throwing movements. Strength training of the chest muscles has the potential to protect the shoulder from injury. Kinematic and kinetic data were acquired in 20 healthy subjects (age: 24.9 ± 2.7 years) using motion capture, force plates for the bench press exercises and load cells in the cable for the cable pulley exercises with 15% and 30% of body weight (BW). Joint ranges of motion (RoM) and joint moments at the shoulder, elbow and wrist were derived using an inverse dynamics approach. The maximum absolute moments at the shoulder joint were significantly larger for the cable pulley exercises than for the bench press exercises. The cable cross-over exercise resulted in substantially different joint angles and loading patterns compared to most other exercises, with higher fluctuations during the exercise cycle. The present results indicate that a combination of bench press and cable pulley exercises are best to train the full RoM and, thus, intra-muscular coordination across the upper limbs. Care has to be taken when performing cable cross-over exercises to ensure proper stabilisation of the joints during exercise execution and avoid joint overloading.